Resistance to 3‐HTMC‐Induced Apoptosis Through Activation of PI3K/Akt, MEK/ERK, and p38/COX‐2/PGE2 Pathways in Human HT‐29 and HCT116 Colorectal Cancer Cells. Issue 12 (26th May 2016) - Semaan, Josiane; Pinon, Aline; Rioux, Benjamin; Hassan, Lama; Limami, Youness; Pouget, Christelle; Fagnère, Catherine; Sol, Vincent; Diab‐Assaf, Mona; Simon, Alain; Liagre, Bertrand
ABSTRACT: Increasing incidence and mortality of colorectal cancer brings the necessity to uncover new possibilities in its prevention and treatment. Chalcones have been identified as interesting compounds having chemopreventive and antitumor properties. In this study, we investigated the effects of the synthetic chalcone derivative 3‐hydroxy‐3′, 4, 4′, 5′‐tetra‐methoxy‐chalcone (3‐HTMC) on proliferation, cell cycle distribution, apoptosis, and its mechanism of action in human colorectal HT‐29 (COX‐2 sufficient) and HCT116 (COX‐2 deficient) cancer cells. We showed that 3‐HTMC decreased cell viability in a dose‐dependent manner with a more potent antiproliferative effect on HCT116 than HT‐29 cells. Flow cytometric analysis revealed G2 /M cell cycle accumulation in HT‐29 cells and significant G2 /M arrest in HCT116 cells with a subsequent apoptosis shown by appearance of Sub‐G1 peak. We demonstrated that 3‐HTMC treatment on both cell lines induced apoptotic process associated with overexpression of death receptor DR5, activation of caspase‐8 and ‐3, PARP cleavage, and DNA fragmentation. In addition, 3‐HTMC induced activation of PI3K/Akt and MEK/ERK principal survival pathways which delay 3‐HTMC‐induced apoptosis in both cell lines. Furthermore, COX‐2 overexpression in HT‐29 cells contributes to apoptosis resistance which explains the difference of sensitivity between HT‐29 and HCT116 cells to 3‐HTMC treatment. Even if resistance mechanisms to apoptosis reduced chalcone antitumoral potential, our results suggest that 3‐HTMC may be considered as an interesting compound for colorectal cancer therapy or chemoprevention. J. Cell. Biochem. 117: 2875–2885, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Our data provided first evidence that 3‐HTMC inhibited cell proliferation of HT‐29 and HCT116 cells by inducing cell cycle arrest before triggering programmed cell death. Furthermore, COX‐2 overexpression in HT‐29 cells may contribute to drug resistance.